2020
DOI: 10.1002/jpen.1768
|View full text |Cite
|
Sign up to set email alerts
|

Value of Nutrition Support Therapy: Impact on Clinical and Economic Outcomes in the United States

Abstract: Objective Healthcare leaders seek guidance on prudent investment in programs that improve patient outcomes and reduce costs, which includes the value of nutrition therapy. The purpose of this project was to conduct an evidence review and evaluate claims analyses to understand the financial and quality impact of nutrition support therapy on high‐priority therapeutic conditions. Methods Task 1 included a review of existing literature from 2013 to 2018 to identify evidence that demonstrated the clinical and econo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 86 publications
0
42
0
4
Order By: Relevance
“…As well, results of a systematic review and meta-analysis showed that nutrition intervention with ONS reduced mortality risk by 35%, reduced complications by 35%, and reduced length of hospital stay by approximately 2 days or approximately 13% reduction [29]. Findings in a recent review and cost analysis indicated that the US Medicare system could save as much as $580 million annually by providing nutrition-focused care in 5 key therapeutic areas (sepsis, gastrointestinal cancer, hospital-acquired infections, surgical complications, and pancreatitis) [30]. Finally, a large multi-center randomized controlled study of 2088 patients in Switzerland (EFFORT trial) demonstrated that early nutrition therapy (ONS provision within 48 h of hospital admission) among malnourished hospitalized patients reduced adverse clinical outcomes including 30-day mortality, while improving functional outcomes and quality of life [31].…”
Section: Discussionmentioning
confidence: 99%
“…As well, results of a systematic review and meta-analysis showed that nutrition intervention with ONS reduced mortality risk by 35%, reduced complications by 35%, and reduced length of hospital stay by approximately 2 days or approximately 13% reduction [29]. Findings in a recent review and cost analysis indicated that the US Medicare system could save as much as $580 million annually by providing nutrition-focused care in 5 key therapeutic areas (sepsis, gastrointestinal cancer, hospital-acquired infections, surgical complications, and pancreatitis) [30]. Finally, a large multi-center randomized controlled study of 2088 patients in Switzerland (EFFORT trial) demonstrated that early nutrition therapy (ONS provision within 48 h of hospital admission) among malnourished hospitalized patients reduced adverse clinical outcomes including 30-day mortality, while improving functional outcomes and quality of life [31].…”
Section: Discussionmentioning
confidence: 99%
“…The approach taken was to model nutrition interventions that could significantly improve clinical outcomes. Specifically, the GI cancer workgroup, a multidisciplinary section of the ASPEN value project, evaluated a targeted review of the literature which combined keywords in the areas of therapeutic nutrition (nutrition, malnutrition), a specific therapeutic area of GI cancers, study parameters (clinical outcomes, healthcare costs) previously conducted by the Value Project team, the complete list of terms used is in Table 2 (24). This search was conducted using PubMed and Google Scholar in 5-year look-back period, for human trials and papers in English, published in both her US & International.…”
Section: Methodsmentioning
confidence: 99%
“…The GI cancer workgroup, then searched for more recent [2018][2019] high-evidence papers [metaanalyses of randomized controlled trials (RCTs), narrative/ systematic reviews of RCTs, recent individual RCTs], using human studies, and papers in English. A literature assessment rubric that was developed by the ASPEN Value Project group was used to evaluate each article identified in the search to select publications for inclusion in the final analysis (24). The rubric, consisted of 4 domains with a point-based scoring system: (I) level of evidence using the GRADE evidence scale (1 to 5), (II) outcomes of interest (0 to 3), (III) type of nutrition intervention (0 to 4), (IV) scalability (1 to 4) (24).…”
Section: Methodsmentioning
confidence: 99%
“…5 Based on this analysis and other work, healthcare decision-makers worldwide have likewise begun to realize that therapeutic nutrition plays important and cost-saving roles in overall care, ie, the value of nutrition care. [6][7][8][9][10] To highlight value in nutrition care, this paper will review evidence of the health and financial tolls of disease-associated malnutrition in hospitals, report realworld results from nutrition-focused quality improvement programs (QIPs) in hospitals, and discuss clinical and policy implications of value in nutrition care for hospitalized patients with disease-associated malnutrition.…”
Section: What Is the "Value" Of Therapeutic Nutrition In Healthcare?mentioning
confidence: 99%